Ride Sharing Behavior in Bangladesh - Fahim Jaman (International Journal of Integrative Research, 2023)
Ride Sharing offerings are becoming more famous each day. In Bangladesh, younger human beings are the usage of this provider. But the helmet great in Bangladesh is not so precise. And more often than not the cost is simply too high than public transport in Bangladesh. Government should take right steps to experience sharing offerings. Contact base ride sharing services isn't secured in Bangladesh.